Digital Public Relations Strategies in Managing the Crisis of Iraqi Refugees in Turkey: An Analytical Study of the Website of the UNHCR Turkey - Hassan, Ramzi Kazem; Aleqabi, Jasim Tarish (ALBAHITH ALALAMI, 2023)
The research aims to identify and diagnose the public relations strategies in its digital online communications by the United Nations High Commissioner for Refugees (UNHCR) in managing the crisis of Iraqi refugees in Turkey. A content analysis form was designed for the digital content of the UNHCR's website dedicated to topics and issues concerning Iraqi refugees that were covered by the site, adopting a comprehensive enumeration approach. The study covered the period from 01/03/2022, to 30/06/2022. The research yielded several key findings, including the predominant use of media, advertising, and education strategies in managing the crisis of Iraqi refugees in Turkey. News and reports ranked first among the media arts used in public relations. There is evident cooperation between the public relations departments of the UNHCR and the Iraqi embassy in Turkey in managing political crises.